The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/1365-2745.14149
|View full text |Cite
|
Sign up to set email alerts
|

Divergent responses of grassland productivity and plant diversity to intra‐annual precipitation variability across climate regions: A global synthesis

Abstract: Global warming intensifies the hydrological cycle and may result in changes in the frequency and intensity of precipitation events. However, a knowledge gap still exists about the general influences of intra‐annual precipitation variability on grassland plant diversity and ecosystem function at the global scale. Here, we synthesized field manipulative experiments from 66 publications to quantify the effects of intra‐annual precipitation variability increases (IPVI) on community biomass and plant diversity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 116 publications
0
2
0
Order By: Relevance
“…Indeed, a recent synthesis found that ANPP responses to altered precipitation patterns were positively correlated with sand content across grasslands globally, further highlighting the potential for edaphic factors like soil texture to mediate ecological responses in water-limited ecosystems (Su et al, 2023). Soil texture has also been found to play an important role in modulating ANPP across deserts in the southwestern US; however, this curiously did not hold true during the summer monsoon in the Chihuahuan Desert (Shepard et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent synthesis found that ANPP responses to altered precipitation patterns were positively correlated with sand content across grasslands globally, further highlighting the potential for edaphic factors like soil texture to mediate ecological responses in water-limited ecosystems (Su et al, 2023). Soil texture has also been found to play an important role in modulating ANPP across deserts in the southwestern US; however, this curiously did not hold true during the summer monsoon in the Chihuahuan Desert (Shepard et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It can alter soil moisture and salinity to influence soil respiration in a variety of ecosystems (Han et al, 2018;Li et al, 2021;Morris et al, 2022). Effects of precipitation events on soil respiration are variable and ecosystem-dependent (Jiang et al, 2013;Su et al, 2023a). For example, strong precipitation is likely to increase soil moisture levels but decrease CO 2 fluxes in tropical rain forests (Cleveland et al, 2010;Zhang et al, Zhang et al 10.3389/fmicb.2024.1328965 Frontiers in Microbiology 02 frontiersin.org 2015).…”
Section: Introductionmentioning
confidence: 99%